Efficacy and Safety of Quadruple-Drug Fixed-Dose Single-Pill Combination Therapy for Hypertension and Dyslipidemia: A Prospective, Multicenter, Observational Study - Park, Soohyung, MD; Park, Eun Jin, MD, PhD; Park, Moon-hwa, MD; Chu, Wonsang, MD; Lee, Dae-In, MD; Roh, Seung-Young, MD, PhD; Choi, Cheol Ung, MD, PhD; Kang, Dong Oh, MD, PhD (Clinical therapeutics, 2025)
Highlights•QFDC therapy provides effective management for both hypertension and dyslipidemia. •QFDC with L/A/R/E successfully achieved target BP and LDL-C levels at 12 weeks. •Combination therapy showed a low rate of adverse events in real-world practice. •Simplified QFDC regimen reduces treatment complexity, enhances patient adherence.